The Growth Revolt: Aftershock of Proposition 13? Booklet - Edmund G. Brown Jr.::::::; Deni Greene::::::; Dean J. Misczynski::::::; Janet Barbaria::::::; Claudia Buckner::::::; Bill McGuire::::::; Elaine Joe::::::; Jacinta Pascoal::::::; Sue Strankiewicz:::::: (1980)
A report detailing the planning efforts to control growth due to the election results of Proposition 13.